2011
DOI: 10.7326/0003-4819-155-12-201112200-00003
|View full text |Cite|
|
Sign up to set email alerts
|

Inviting Patients to Read Their Doctors' Notes: Patients and Doctors Look Ahead

Abstract: Background Little is known about what primary care physicians (PCPs) and patients would expect if patients were invited to read their doctors' office notes. Objective To explore attitudes toward potential benefits or harms if PCPs offered patients ready access to visit notes. Design The PCPs and patients completed surveys before joining a voluntary program that provided electronic links to doctors' notes. Setting Primary care practices in 3 U.S. states. Participants Participating and nonparticipating P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 18 publications
4
155
2
8
Order By: Relevance
“…23,24 Second, physicians may worry that patient portals might generate a large volume of clinical issues that require responses (time for which the physician cannot bill). 25 And finally, some providers are concerned that accessing these data might make patients confused or worried.…”
Section: Exhibitmentioning
confidence: 99%
“…23,24 Second, physicians may worry that patient portals might generate a large volume of clinical issues that require responses (time for which the physician cannot bill). 25 And finally, some providers are concerned that accessing these data might make patients confused or worried.…”
Section: Exhibitmentioning
confidence: 99%
“…[17][18][19][20] In brief, we learned that patients were enthusiastic about the experience and reported potentially important clinical benefits, such as improved recall and understanding of their care plan, improved adherence to their medications, and feeling more in control of their care. We found that doctors were surprised by how few patients appeared troubled by what they read and how little effect the intervention had on the PCPs' work lives.…”
Section: An Initial Foray Into Primary Carementioning
confidence: 99%
“…Population-based surveys suggest that patients desire online access to their medical records and email communication with clinicians [21]. Patients expect the capability of controlling accesses to their data and hiding some of their data from health care practitioners.…”
Section: Consumer Expectationmentioning
confidence: 99%
“…Reports show that 80% of health care personnel use their smartphones for workrelated tasks [20,21]. The system thus becomes an environment, where a whole ecology of applications may be coexisting in the device opening the door to many unintentional but malicious threats [22].…”
Section: Data Breachesmentioning
confidence: 99%